MODEL PERAN PERADILAN ETIK DALAM MERAIH KEPERCAYAAN PUBLIK (Studi Kasus Penyelenggara Pemilu Berintegritas Dewan Kehormatan Penyelenggara Pemilu Periode 2012-2017) - Gusfa, Henni; Irmawanti, Irmawanti (Journal Communication Spectrum : Capturing New Perspectives in Communication, 2017)
This study describes communication constitutes organizing the Election OrganizerHonorary Council (DKPP) in realizing election organizers with integrity. Using the casestudy method, the results show that, 1) DKPP is a judicial role model of the professionalcode of ethics which in its work shows its integrity with innovation through open judicial,2) effective communication among fellow members in preparing membershipformations, as well as with related parties such as the Secretariat General of the ElectionSupervisory Body (Bawaslu) and the Ministry of State Apparatus Empowerment andBureaucratic Reform (Kemenpan-RB) in formulating the structure of the DKPPsecretariat, 3) communication with key partners namely the General ElectionCommission and Bawaslu to legalize the code of ethics, 4) communication in the divisionof work among DKPP membersKeywords: Organisation communication, communicationconstitutive organisation, DKPP, ethic code judicature, integrity election organizer.